Early-stage thermal performance design of thermo-active walls implemented in underground infrastructures. (June 2022) - Zannin, Jacopo; Ferrari, Alessio; Larrey-Lassalle, Pyrène; Laloui, Lyesse
Abstract: Energy geostructures (EGs) represent an innovative technology in the sustainable energy agenda and are useful for satisfying the energy needs of the built environment. They are usually involving geostructures such as piles, walls, tunnels, shafts, and sewers. The application of such technology to infrastructure projects may have considerable thermal potential because of the large surfaces that can be thermally activated. This study focuses on thermo-active walls (energy walls, EWs), which are retaining structures used to sustain the sides of excavations. Key features related to their thermal design are examined, and a design methodology is proposed. The heat-exchange modes involving EWs and the surrounding materials (concrete, soil, air) are investigated via extensive three-dimensional hydrothermal finite-element simulations involving the non-isothermal flow in the heat exchangers (HEs), as well as all other heat-exchange modes. The results are first presented as charts related to the thermal behavior of the HEs under different hydrothermal environments. Finally, a methodology for early-stage thermal performance design is proposed, and a corresponding flowchart is presented. This study may be helpful for incorporating EGs into the engineering design. Highlights: Thermo-active underground infrastructures for providing green energy to the neighborhoods of the future. A methodology for thermal design is presented, enabling engineers to detect thermal potential of sites. Correct optimization of the heat exchanger design doubles the thermal potential. A flowchart is presented for determining the thermal performance design values. Underground energy infrastructures are capable of delivering thermal power of 10 ÷ 50 W / m 2 .